2021
DOI: 10.1038/s41598-021-84547-5
|View full text |Cite
|
Sign up to set email alerts
|

Latent traits of lung tissue patterns in former smokers derived by dual channel deep learning in computed tomography images

Abstract: Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease and the traditional variables extracted from computed tomography (CT) images may not be sufficient to describe all the topological features of lung tissues in COPD patients. We employed an unsupervised three-dimensional (3D) convolutional autoencoder (CAE)-feature constructor (FC) deep learning network to learn from CT data and derive tissue pattern-clusters jointly. We then applied exploratory factor analysis (EFA) to discover the unobser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…After adjusting for FEV1, there are still sLTPs showing significant correlations with MRC dyspnea scale, 6MWT total distance, baseline and post-6MWT oximetry. Overall, our correlation levels compare well with [ 35 ] performed on a similar cohort size, but with highest COPD-prevalence, while reporting fewer significant positive correlations when proposing 7 radiological emphysema subtypes (called “factors”) learned from 80 emphysema visual patterns. Correlations with standard emphysema subtypes, using similar models, were studied for the same population in [ 4 ].…”
Section: Discussion and C Onclusionsupporting
confidence: 82%
“…After adjusting for FEV1, there are still sLTPs showing significant correlations with MRC dyspnea scale, 6MWT total distance, baseline and post-6MWT oximetry. Overall, our correlation levels compare well with [ 35 ] performed on a similar cohort size, but with highest COPD-prevalence, while reporting fewer significant positive correlations when proposing 7 radiological emphysema subtypes (called “factors”) learned from 80 emphysema visual patterns. Correlations with standard emphysema subtypes, using similar models, were studied for the same population in [ 4 ].…”
Section: Discussion and C Onclusionsupporting
confidence: 82%
“…Biswas et al reported the prevalence of these lobes as 2.17% and 1.08%, respectively [ 5 ]. Patients with an accessory airway branch have been associated with a 1.64 higher risk of chronic obstructive pulmonary disease (COPD) and bronchitis [ 6 - 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning based tissue-pattern phenotypes can be further combined with qCT imaging-based variable for subtyping. 55 Identification of longitudinal COPD subgroups may help us understand the path of disease progression and provide prognostic information to help determine more appropriate, patient-oriented therapies.…”
Section: Discussionmentioning
confidence: 99%